(untitled) (Indian Journal of Nematology, 2024)
The aim of the present study was to develop a protocol for stacking multiple genes through Agrobacterium mediated cotransformation in tomato. Agrobacterium strains GV-3101 and LB4404 carrying Meloidogyne incognita specific dsRNA of Integrase and ToLCV specific dsRNA of AC4 constructs respectively were used for co-transformation in order to provide dual resistance against both the pathogens. Binary vectors pBC-142 and pCAMBIA-2301 were used for cloning Integrase and AC4 hairpin RNA respectively. Zeatin riboside (1mg/L) and IAA (0.5mg/L) were used as plant hormones in the pre-culture, shoot induction and shoot elongation medium while only IAA (0.5mg/L) was used for rooting media. Transformed plants were molecularly confirmed for the presence of nptII (Kanamycin resistance gene), Integrase and AC4 genes by PCR. A transformation frequency of 62.50% was obtained for the co-transformed dual constructs based on PCR positive transgenic plants as compared to 82.60% for the single construct. The results strongly verify multiple genes stacking in tomato through co-transformation which is reported for the first time in tomato. This protocol also paves way for developing resistance against two different pathogens by host generated RNAi through co-transformation.